2011
DOI: 10.1063/1.3600897
|View full text |Cite
|
Sign up to set email alerts
|

A Zeeman slower design with permanent magnets in a Halbach configuration

Abstract: We describe a simple Zeeman slower design using permanent magnets. Contrary to common wire-wound setups no electric power and water cooling are required. In addition, the whole system can be assembled and disassembled at will. The magnetic field is however transverse to the atomic motion and an extra repumper laser is necessary. A Halbach configuration of the magnets produces a high quality magnetic field and no further adjustment is needed. After optimization of the laser parameters, the apparatus produces an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 12 publications
3
51
0
1
Order By: Relevance
“…In row (viii) we give the associated magnetic field span |B L | and we see that it is generally of order a few hundred gauss, hence large coils with hundreds of amp-turns are usually constructed. Alternative schemes have been successfully demonstrated, e.g., deploying arrays of permanent magnets 46,[59][60][61] or a single winding with a variable pitch. 62 For Li and Na the required field span becomes rather large which stems ultimately from their small mass and associated large oven e↵usion speed.…”
Section: A Practical Implications Of Basic Modelmentioning
confidence: 99%
“…In row (viii) we give the associated magnetic field span |B L | and we see that it is generally of order a few hundred gauss, hence large coils with hundreds of amp-turns are usually constructed. Alternative schemes have been successfully demonstrated, e.g., deploying arrays of permanent magnets 46,[59][60][61] or a single winding with a variable pitch. 62 For Li and Na the required field span becomes rather large which stems ultimately from their small mass and associated large oven e↵usion speed.…”
Section: A Practical Implications Of Basic Modelmentioning
confidence: 99%
“…Our Zeeman slower design follows the same architecture than the one described in [12] adapting its shape to fit sodium atoms specifici-ties. As in [12], we work with an increasing magnetic field configuration. As a result, the laser beam addresses the |F = 2, m F = −2 to |F = 3, m F = −3 transition, where F and F represent respectively the total angular momentum of the ground and excited states and m F and m F their projections onto the quantization axis.…”
Section: Experimental Designmentioning
confidence: 99%
“…3 (b) and (d)). Since the shape of the ideal magnetic field profile is quite steep toward the end, an additional ring made of 10 mm-side cubic magnets of N35 grade (B R = 11.7 kG) is added at the end of the structure [12]. In order to adjust the geometry of the Zeeman slower shown in Fig.…”
Section: Experimental Implementationmentioning
confidence: 99%
“…After cleaning and drying, the spiral was impregnated with epoxy glue. We used commercial low viscosity, room-temperature curing epoxy 3 , loaded with 10% of 0.25 µm fiber glass flake and 30% aluminium nitride (AlN) powder 4 . Preliminary tests showed that cracks can develop in the inter-windings regions due to thermal stress when using high temperature curing expoxy, hence the use of a fiber glass load to reinforce the structure.…”
Section: Coil Bodymentioning
confidence: 99%
“…As experimental apparatus become more and more complex, with more laser beams or high-aperture imaging systems to accommodate, space occupation as well as heat management constraints become more and more acute, calling for optimized and flexible electromagnet designs. Efforts in this direction have been reported in the past years, in particular novel designs for Zeeman slowers [3,4], Bitter electromagnets [5][6][7] or improved heat management methods [8]. More compact systems of magnetic traps use in-vacuum electromagnets [9][10][11], or atom chips [12,13], but those are not adapted to experiments requiring large homogeneous fields.…”
Section: Introductionmentioning
confidence: 99%